Unexpected species diversity within Sri Lanka’s snakehead fishes of the Channa marulius group (Teleostei: Channidae) - Sudasinghe, Hiranya; Adamson, Eleanor A. S.; Ranasinghe, R.h. Tharindu; Meegaskumbura, Madhava; Ikebe, Chiho; Britz, Ralf (Zootaxa, 2020)
The taxonomic status of the large snakeheads of the Channa marulius group that occur in Sri Lanka is reviewed and clarified. Two species are recognized from the island, based on both morphological and molecular (cytochrome c oxidase subunit 1: cox1) differentiation: C. marulius Hamilton from the northern dry zone and C. ara Deraniyagala from the middle and lower regions of the Mahaweli basin. Channa ara is endemic to Sri Lanka and can be distinguished from its Marulius group congeners, C. marulius, C. aurolineata and C. auroflammea, by having fewer dorsal- and anal-fin rays, fewer lateral-line scales and fewer vertebrae; from C. marulioides by a different adult colour pattern; and from C. pseudomarulius by having more vertebrae. At the cox1 barcoding locus, Channa ara is at least 3.6% genetically different from C. marulius, and at least 8% different from the other described species in the group. Specimens collected from the southwestern wet zone in Sri Lanka are a puzzling third component of the Marulius group’s diversity, uncovered in this study, and identified here as C. cf. ara. Whilst genetically more similar to C. marulius, C. cf. ara possesses fewer dorsal- and anal-fin rays, fewer lateral-line scales and fewer vertebrae and is therefore morphologically more similar to C. ara. Channa ara can be distinguished from C. cf. ara, however, by differences in circumpeduncular scale count, adult colour pattern, and by an uncorrected pairwise genetic distance of 3.7% in cox1 sequences. A neotype is designated for Ophicephalus marulius ara Deraniyagala.